Gender, Age, Educational Maturity In Relation To Job Satisfaction: An examination of job satisfaction and its relationship with gender, age, and educational qualification (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The present study examines job satisfaction in context of some demographic variable such as age, gender, and educational qualification. 302 employees ranging from 23 to 55 years of age with different educational background, Viz., under-graduates, graduates, other technical diplomas and post-graduates, were selected form city of Ahmedabad, Gujarat. Out of 250 were males and 52 were females as fewer females responded to the questionnaire to volunteer responses. The analysis indicated that job satisfaction is significant related to these entire variable.